Training effect on balance control in young alpine skiers: ground reaction force study - Kasovic, M.; Mejovsek, M.; Cigrovski, V.; Loncar, V. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Balance is a very complex motor ability that involves keeping a specified Position on a small area, ground or object. If we observe the definition through the different situations on the skis, it can simply be concluded that balance is closely related to skiing. In order to maintain balance on the skis, muscle force as well as neuromuscular coordination is important to a skier because they enable him/her to maintain stability and balance in every moment. Therefore, muscle fatigue might have significant influence on stability and efficiency in skiing.